The structural transition of bimetallic Ag–Au from core/shell to alloy and SERS application. Issue 41 (29th June 2020) - Ha Pham, Thi Thu; Vu, Xuan Hoa; Dien, Nguyen Dac; Trang, Tran Thu; Van Truong, Nguyen; Thanh, Tran Dang; Tan, Pham Minh; Ca, Nguyen Xuan
Abstract : It is well-known that Ag–Au bimetallic nanoplates have attracted significant research interest due to their unique plasmonic properties and surface-enhanced Raman scattering (SERS). Abstract : It is well-known that Ag–Au bimetallic nanoplates have attracted significant research interest due to their unique plasmonic properties and surface-enhanced Raman scattering (SERS). In recent years, there have been many studies on the fabrication of bimetallic nanostructures. However, controlling the shape, size, and structure of bimetallic nanostructures still has many challenges. In this work, we present the results of the synthesis of silver nanoplates (Ag NPls), and Ag–Au bimetallic core/shell and alloy nanostructures, using seed-mediated growth under green LED excitation and a gold salt (HAuCl4 ) as a precursor of gold. The results show that the optical properties and crystal structure strongly depend on the amount of added gold salt. Interestingly, when the amount of gold( x ) in the sample was less than 0.6 μmol ( x < 0.6 μmol), the structural nature of Ag–Au was core/shell, in contrast x > 0.6 μmol gave the alloy structure. The morphology of the obtained nanostructures was investigated using the field emission scanning electron microscopy (FESEM) technique. The UV–Vis extinction spectra of Ag–Au nanostructures showed localized surface plasmon resonance (LSPR) bands in the spectral range of 402–627 nm which changed from two peaks to one peak as the amount of gold increased. Ag–Au core/shell and alloy nanostructures were utilized as surface enhanced Raman scattering (SERS) substrates to detect methylene blue (MB) (10 −7 M concentration). Our experimental observations indicated that the highest enhancement factor (EF) of about 1.2 × 10 7 was obtained with Ag–Au alloy. Our detailed investigations revealed that the Ag–Au alloy exhibited significant EF compared to pure metal Ag and Ag–Au core/shell nanostructures. Moreover, the analysis of the data revealed a linear dependence between the logarithm of concentration (log C ) and the logarithm of SERS signal intensity (log I ) in the range of 10 −7 –10 −4 M with a correlation coefficient ( R 2 ) of 0.994. This research helps us understand better the SERS mechanism and the application of Raman spectroscopy on a bimetallic surface.